Co-Creation and Crowdsourced Innovation: A Strategic Approach to Building Consumer Loyalty - Merdika Mansur, Daduk (Manunggal Halim Jaya, 2026)
In the era of digital transformation and empowered consumers, co-creation and crowdsourced innovation have emerged as strategic approaches to enhance consumer loyalty. This study aims to explore the extent to which consumer participation in co-creation and crowdsourced innovation initiatives influences brand loyalty, particularly within the Indonesian market context. Employing a descriptive quantitative methodology, the research collected data through structured online surveys administered to a diverse sample of consumers who had previously engaged in co-creative or crowdsourced brand activities. The study investigates the prevalence and types of participation, perceived value outcomes, and correlations with loyalty indicators such as trust, satisfaction, emotional attachment, and advocacy. The findings reveal that active involvement in co-creation significantly correlates with increased brand loyalty, particularly among digitally literate and younger consumers. Crowdsourced innovation, when perceived as authentic and impactful, enhances consumer identification with the brand and strengthens advocacy behaviors. Moderating factors such as digital readiness, demographic characteristics, and cultural orientation were found to influence the strength of these relationships. The study also highlights the importance of brand transparency, perceived control, and value congruence in shaping consumer perceptions and behavioral outcomes. These insights offer practical implications for marketers seeking to design participatory strategies that resonate with diverse consumer segments and foster long-term loyalty. Furthermore, the study contributes to theoretical development by integrating Service-Dominant Logic, Customer Engagement Theory, and psychological ownership frameworks into a unified model of participatory consumer-brand relationships.